1980
DOI: 10.1111/j.1752-1688.1980.tb02543.x
|View full text |Cite
|
Sign up to set email alerts
|

FLOODPLAIN MANAGEMENT NEEDS PECULIAR TO ARID CLIMATES1

Abstract: Many practices followed uniformly nationwide in the federal flood control and floodplain management programs are inappropriate or even counter productive in the arid Utah climate. An analysis of the 130‐year Utah flood history, the structural and nonstructural flood programs in the state, and local perceptions obtained by field visits and interviews in 35 Utah communities revealed a number of such inefficiencies. Since flood flows dissipate quickly when they emerge from mountain watersheds onto desert lowlands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
1983
1983

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…From 1936 until the mid-1960's the shift began to the combined structural and nonstructural approach, which continues in the 1980's. James (1979) has suggested that the state level may. be the most appropriate for designing and implementing flood hazard management.…”
Section: State Responsibilitymentioning
confidence: 97%
“…From 1936 until the mid-1960's the shift began to the combined structural and nonstructural approach, which continues in the 1980's. James (1979) has suggested that the state level may. be the most appropriate for designing and implementing flood hazard management.…”
Section: State Responsibilitymentioning
confidence: 97%